Tazkiyatun Nufus dalam buku Madarij As-Salikin: Strategi Penyuluhan Islam dalam Penyucian Jiwa di Pondok Pesantren Nurul Huda Mangkang Wetan - Anwar, Muhammad Choirul; Murtadho, Ali (Jayapangus Press, 2025)
This study examines the concept of Tazkiyatun Nufus in the book Madarij As-Salikin by Ibnu Qayyim Al-Jauziyah as an Islamic counseling strategy in the process of purifying the soul, with a focus on its implementation at the Nurul Huda Islamic Boarding School in Mangkang Wetan. Amidst the challenges of modern life that is full of pressure and temptation, students as the next generation of the community also face spiritual problems, both from within themselves and their social environment. This study uses a qualitative approach with a literature study method and content analysis, which explores the principles of tazkiyatun nufus such as takhalli, tahalli, and tajalli as well as practical strategies such as dhikr, muhasabah, tafakkur, and mujahadah that are relevant in the context of Islamic counseling. The results of the study indicate that Madarij As-Salikin not only offers a profound Sufi concept, but is also able to be an applicable guide in forming a clean soul and noble morals. This study also reveals the real problems faced by students, namely the struggle between knowledge and lust, as well as the inequality of social relations between students that can hinder the process of purifying the soul. Therefore, an integrated Islamic counseling strategy with the values ​​of tazkiyatun nufus needs to be developed so that it can touch the spiritual, emotional, and social dimensions as a whole, so as to form a complete and characterful Muslim person.